New multifunctional sulfonato-containing metal phosphonates proton conductors - Salcedo, Inés R.; Bazaga-García, Montse; Pérez-Colodrero, Rosario Mercedes; Xanthopoulos, Konstantinos; Demadis, Konstantinos D.; Stock, Norbert; Cabeza-Díaz, Aurelio; Ramírez-Losilla, Enrique; Olivera-Pastor, Pascual (My University, 2018)
Anchoring of acidic functional groups to organic linkers acting as ligands in metal phosphonates has been demonstrate to be a valid strategy to develop new proton conductor materials, which exhibit tunable properties and are potentially applicable to proton exchange membranes, such as those used in PEMFCs [1,2]. In this work, the structural and proton conductivity properties of several families of divalent and trivalent metal amino-sulfophosphonates are presented. The chosen ligand, (H2O3PCH2)2-N-(CH2)2-SO3H, was reacted with the appropriate metal salt using highthrough-put screening and/or microwave-assisted synthesis. Different crystal structures haven been solved displaying a variety of metal ligand coordination modes, in whose frameworks acidic groups contribute to create strong H-bond networks; together with lattice and bound water molecules. Proton conductivity values oscillate between 10-4 and 10-2 S.cm-1, at 80 ºC and 95 % relative humidity, most of them showing activation energies characteristic of a Grotthuss-type proton transport mechanism.
Keywords: Protones; Metal phosphonates; Proton conductivity; Coordination polymers; Hybrid materials